PENINGKATAN KAPASITAS KADER DESA DALAM MENCEGAH DAN MENGENDALIKAN DIABETES MELITUS MELALUI PROMEDIA (PROGRAM EDUKASI MANAJEMEN DIABETES MELITUS) - Iin Patimah; Tantri Puspita; Rudy Alfiyansah; Andhika Lungguh Perceka (LP4M STIKes Karsa Husada Garut, 2023)
Health cadres trained in Diabetes Mellitus (DM) are needed to help improve regional health. Training and educational actions to prevent and control Diabetes Mellitus in the form of PROMEDIA (Diabetes Mellitus Management Education Program) can be useful activities to improve the level of public health at large. This activity was carried out for 2 days in the Hall of the Tarogong Community Health Center with the presence of 30 Health cadres. The results of measuring calorie need showed that, the Temporary Blood Sugar (GDS) of the cadres present ranged from 88 mg/dl -316 mg/dl (mean= 134 mg/dl), calorie needs ranged from 1236 cal – 2415 cal (mean= 1524 cal). The results of health education show that 76% of cadres experienced an increase in knowledge after being given education. This Promedia activity showed benefits especially for cadres, including increasing knowledge about diabetes mellitus management, skills in checking blood sugar levels, calculating daily calorie needs and daily follow-up mechanisms.